ANTIBACTERIAL ACTIVITY OF GARCINIA KOLA EXTRACTS AGAINST CLINICAL ISOLATES OF STREPTOCOCCUS PYOGENES IN ZARIA, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Garcinia kola, commonly called bitter kola is known mostly for its antimicrobial potentials. Moreover, Streptococcus pyogenes a Gram-positive, facultative anaerobe, and non-spore forming bacterium that occur in long chains cocci is unique in causing different bacterial infection, hence a need for alternative therapy. Therefore, this study was carried out to evaluate the antimicrobial activities of Garcinia kola seed extracts against clinical isolates of Streptococcus pyogenes in Zaria, Nigeria. In this study, Streptococcus pyogenes was isolated from throat swabs and sputum of patients with respiratory illnesses attending a selected clinic in Zaria using chocolate agar and further characterized using standard biochemical test. Isolates were stored on agar slants at 40C for further use. Thereafter, aqueous and n-butanol, extraction of dried seeds of Garcinia kola was carried out using Soxhlet extraction method. Phytochemical screening of the extract was determined using standard techniques while antimicrobial activities against the stored bacterium were determined using Kirby Bauer method. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were determined using previous standard microbiological technique. Photochemistry of the extract showed the presence of tannin, saponin, alkaloid, phenol, steroids, and flavonoid. Highest (16-28mm) and lowest (6-8mm) antimicrobial activities against the bacteria were observed among n-butanol and aqueous extract respectively while MIC and MBC of n-butanol were 0.31 and 0.63 mg/ml respectively. The antibacterial activities of the extracts observed in this study, justify the use of this plant for the treatment of infections caused by these organism in traditional medicine.
Keywords: Garcinia kola, Phytochemicals, Streptococcus pyogenes, MIC, MBC